Pemberdayaan Kader Lansia Melalui Pelatihan Kesehatan Dan Pelatihan Hidroponik - Taufan Citra Darmawan; Saut Horas Hamonangan Nahampun; Dianita Primihastuti (STIKes William Booth Surabaya, 2022)
Special challenges for the elderly in the health sector such as the emergence of degenerative problems, non-communicable diseases, and mental health problems as well as economic problems in the form of reduced work productivity, limited employment opportunities, and poverty are the biggest threats to the welfare of the elderly. Most of the elderly in the Mojotengah, Menganti, Gresik areas only do their daily activities at home. Many elderly people experience health problems but do not seek treatment due to distance and financial constraints. Therefore it can be said that the area has the potential to develop the potential of the elderly. The purpose of this activity is to form elderly cadres and conduct training on health checks and pioneering a hydroponic business as a means to improve the standard of living of the elderly The implementation method is carried out by forming elderly cadres aged over 55 years. 30 residents were selected to become elderly cadres who then carried out 2 trainings consisting of training on inspection and use of medical devices as well as hydroponic training. Activities are carried out once a month. The results of the implementation of the empowerment of the elderly in the Mojotengah area replace Gresik, namely that cadres have been formed. Cadres are not only at the RW level but also representatives of each RT. After training on the use of medical devices in collaboration with the puskesmas, the elderly cadres who had been trained were able to apply these activities. Besides that, after the hydroponic training, most of the plants managed to grow quite well, the plants produced can be consumed, only the quality of the plants produced is still not optimal due to differences in temperature and air quality, so that in the future it is hoped that further programs can be carried out related to the problem of hydroponic planting and marketing.